Research status and frontiers in liver cancer immunotherapy: a bibliometric perspective on highly cited literature - Pan Su; Yeqiong Han; Jindong Yi; Yu Hou; Yao Xiao; Yao Xiao; Yao Xiao (Frontiers in Oncology)
BackgroundLiver cancer is one of the major causes of cancer-related death in the world. As a breakthrough therapy, immunotherapy had significantly improved the prognosis of patients. However, the current research status and research hotspots in the field of liver cancer immunotherapy still lack systematic review. Based on the bibliometric analysis of highly cited papers, this study intended to reveal the current research status, research hotspots and future research trends in this field.ObjectiveThe purpose of this study was to analyze the national/regional contributions, authors and institutions cooperation network, keywords clustering and keywords burst analysis of highly cited papers on liver cancer immunotherapy through bibliometrics, so as to clarify the research frontier and development direction, and provide objective data support for future research direction and clinical practice.MethodsThe highly cited papers on liver cancer immunotherapy from the Web of Science core collection up to February 23, 2025 were retrieved, and 232 studies were included. CiteSpace was used to build a knowledge map, analyze the distribution of years, countries, authors, institutions and cooperation networks, and identify research hotspots and emerging trends through keyword clustering and burst detection.ResultsThe number of highly cited papers continued to increase from 2014 and reached a peak in 2022. China and the United States had the highest number of publications and the centrality of cooperation networks. The author with the highest number of papers was Llovet, Josep M, whose research direction mainly focused on immune checkpoint inhibitor combination therapy and molecular typing. The author with the highest cooperation network centrality was Duda, Dan G, whose research team focused on tumor microenvironment regulation. Harvard University and the University of Barcelona played an important central role in the institutional collaboration. Keywords analysis showed that immune checkpoint inhibitors, tumor microenvironment and combination therapy were the core of liver cancer immunotherapy. Burst keywords such as cell lung cancer, pembrolizumab, advanced melanoma, blockade, lymphocytes, etc. had revealed the research frontier of liver cancer immunotherapy research.ConclusionThe research on liver cancer immunotherapy had made multi-dimensional progress, with China and the United States leading the global cooperation. The main research directions were the combination strategy of immunization, the regulation of tumor microenvironment and the exploration of novel targets. In the future, it is necessary to optimize treatment resistance solutions, integrate interdisciplinary resources, and promote the development of precision and personalized treatment.